PENGEMBANGAN LMS “PASTI SOBAT SMP” UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM DIGITALISASI PEMBELAJARAN DI TINGKAT SMP - Gulbudin Hekmatyar; Widia Winata (Fakultas Pendidikan Islam dan Keguruan Universitas Garut, 2026)
This study aims to develop and assess the feasibility of the “PASTI Sobat SMP” LMS, a digital training platform designed to support teachers in improving their competencies in utilizing educational technology and digitalization aid tools. The research employs a mixed-methods approach and a Research and Development (R&D) method based on the ADDIE model, carried out through the stages of needs analysis, design, content development, trial implementation, and formative and summative evaluation. The findings indicate that the developed LMS meets the “highly feasible” category based on expert validation. Field trials reveal that teachers can use the LMS easily, show increased engagement, and perceive benefits in managing digital learning. Observation and interview data also show that the use of quiz and discussion forum features enhances student learning activities. However, several challenges remain, such as internet connectivity issues and variations in digital literacy. Overall, the “PASTI Sobat SMP” LMS proves effective as a digital training platform and has the potential to accelerate learning transformation in junior high schools. The study recommends strengthening mentoring programs and ensuring equitable access to technology for sustainable implementation.